A future agenda for research on climate change and human mobility - Robert Oakes; Kees Van~der~Geest; Benjamin Schraven; Stephen Adaawen; Sonja Ayeb-Karlsson; Alexander de Sherbinin; Benjamin Etzold; Juliane Groth; Kathleen Hermanns; Silvana Lakeman; Raphael Nawrotzki; Christina Rademacher-Schulz; et al. (International Migration, 2023)
In the past 150.167emyears, research activities focusing on the interlinkages between climate change and human mobility have intensified. At the same time, an increasing number of actors and processes have sought to address human mobility in the context of climate change from a policy perspective. Hitherto, research has been limited in terms of geographical preferences as well as conceptual and methodological focus areas. This paper argues that to address the evolving policy space, future research on climate change in the context of human mobility needs to become more differentiated, integrated and generalized. This includes concerted efforts to better integrate researchers from the global South, improved cross-linkages between different datasets, approaches and disciplines, more longitudinal and comparative studies and development of innovative qualitative and quantitative methods.
Keywords: 300